Pengaruh Berat Katalis Zeolit Alam terhadap Pencairan Limbah Ban dalam Bekas Kendaraan Bermotor Roda Dua Menjadi Bahan Bakar Cair - Lince Muis; Ira Galih Prabasari; Nana Suyana (Universitas Batanghari Jambi, 2019)
The productivity of Indonesia's tire industry is expected to be higher following the growth of domestic and global motor vehicle production. Along with that, waste used tires that are not used in the environment are increasing. Rubber-based tires, is one type of synthetic polymer (Polystyrene). Polystyrene cannot be easily recycled so that the processing of polystyrene waste must be done properly so as not to harm the environment. Polystyrene pyrolysis process is one way to minimize the polystyrene waste. The pirlolysis process is carried out with temperature operating conditions of 400 oC, weight of tire rubber 3000 grams with variations of catalyst 2%, 4% and 6% for 3 hours. The results showed that the more catalysts used the% CHP Conversion produced would be greater, the best results on the 6% catalyst were as much as 41.073%. Based on the results of the analysis using GC-MS, Used inner tire pyrolysis oil has the following hydrocarbon chains: (C1-C5) as much as 0.33%, (C5-C12) as much as 88.96% and (C10-C28) 10.71%. Hydrocarbon compounds contained in the oil from used tire pyrolysis contain many aromatic compounds